AURAT PEREMPUAN BAGI LAKI-LAKI AJNᾹBῙYYAH PERSPEKTIF FIQH MUQᾹRANAH TINJAUAN HISTORI - La Aludin Ladaa (TAHKIM, 2017)
Clothes get serious attention in Islamic law, because it is closely related to the provision close the genitals. Close the genitals including the specific characteristics of Muslims once a differentiator with people of other faiths. Genitalia woman covering her entire body, except the face and palms of his hands, so it is not allowed to be seen by men ajnabiyyah. In this regard the scholars of different schools of fiqh opinions. However, the scholars agreed that the real point of the command closes the nakedness contains four principles, namely (1) command to hold a view of which has been forbidden by Allah; (2) an order to keep the pubic of the unlawful act; (3) prohibition to reveal jewelry except the usual look; (4) an order to shut the khumur to the chest, better known as the hijab by Muslim community in Indonesia. In addition, the scholars also agree that the school of Islam which deny law must cover the nakedness without aging, is considered an infidel. Keywords: female genitalia, male ajnabiyyah, muqaran fiqh, history